2021
DOI: 10.3390/nu13124565
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Composition and Health-Promoting Effects of the Grewia Species—A Systematic Review and Meta-Analysis

Abstract: Globally grown and organoleptically appreciated Grewia species are known as sources of bioactive compounds that avert the risk of communicable and non-communicable diseases. Therefore, in recent years, the genus Grewia has attracted increasing scientific attention. This is the first systematic review which focusses primarily on the nutritional composition, phytochemical profile, pharmacological properties, and disease preventative role of Grewia species. The literature published from 1975 to 2021 was searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 94 publications
(150 reference statements)
0
9
0
Order By: Relevance
“…It can be stated that high antioxidant activity could be attained by adding the bioactive compounds quantified in this study. A plethora of literature showed a positive relationship between specific bioactive compounds and antioxidant activity [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In an earlier study, the antioxidant activity of OB-EO was reported as IC 50 6.68 mg/mL and 62.2 mg ascorbic acid equivalent (AAE)/g in DPPH and FRAP assay, respectively, and was ascribed to the presence of α-pinene, γ-terpinene, 1,8-cineole, limonene, linalool, and linalyl acetate [ 45 ], supporting the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It can be stated that high antioxidant activity could be attained by adding the bioactive compounds quantified in this study. A plethora of literature showed a positive relationship between specific bioactive compounds and antioxidant activity [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In an earlier study, the antioxidant activity of OB-EO was reported as IC 50 6.68 mg/mL and 62.2 mg ascorbic acid equivalent (AAE)/g in DPPH and FRAP assay, respectively, and was ascribed to the presence of α-pinene, γ-terpinene, 1,8-cineole, limonene, linalool, and linalyl acetate [ 45 ], supporting the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…There were around 30 identified compounds, in which tetracontane showed maximum area % and has already been reported to show antimicrobial and antioxidant properties [17][18][19][20][21]. In the literature, GCMS of Grewia tenax methanol-based fruit extract showed the presence of 82 compounds, predominantly 5,9-undecadien-2-ol, 6,10-dimethyl-as 11.60% whereas in aqueous extract it was 3.18% [10,17]. The green synthesis of AgNPs using GTB extracts showed a change in colour from light yellowish brown to dark brown within 10 min at room temperature and under continuous shaking.…”
Section: Quantitative Phytochemical Analysis Of Grewia Tenax Bark By ...mentioning
confidence: 99%
“…Grewia tenax is a tropical, deciduous shrub and a potentially threatened species of the Thar Desert of India. It is a multipurpose but underutilised species having antioxidant, anticholinesterase and antibacterial properties [10]. The plant contains phytochemicals such as alkaloids, saponins, tannins, flavonoids, terpenoids, etc [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nagabala acts as a rasayana so it promotes both physical and mental health, and also improves the status of rasa dhatu. It contains compounds like oleic acid, linoleic acid, terpenes, myristic acid, gingerol, aldehyde, and alcoholic compounds, the leaves of Nagabala contain an alkaloid named ephedrine and pseudoephedrine, its roots and seeds also contain ephedrine, vasicinol, N-Methyl tryptophan which having cardiovascular, analgesic, antiinflammatory, and antioxidant effects (24).…”
Section: Madhura Rasa Ushna-tikshan and Sukshma Gunas S R O T O V I S...mentioning
confidence: 99%